Effects of Exposure to Cotton Dusts on FVC, FEV1, and FEV1/ FVC% in Male Cotton dust Workers - Hasanat, Md Abul; Sarkar, Chandra Rani; Zahid, ATM Zoadur Rahim (Journal of Bangladesh Society of Physiologist, 2016)
Background: Workers in environment with cotton dust exposure are at risk of development of occupational pulmonary functional disorder. Objectives: To observe the effects of cotton dust exposure on FVC, FEV1, FEV1/FVC% in male cotton dust worker. Methods: This cross-sectional study was carried out in the department of physiology, Rangpur Medical College, Rangpur from 2014july to 2015July. Total 25 apparently healthy non-smoker male workers aged 20-40 years, exposed to cotton dust for at least 6 months, were selected from different fabric weaving and cotton ginning factories of Rangpur district. Twenty five age & BMI matched apparently healthy male subjects, not exposed to cotton dusts were taken as control. FVC, FEV1 and FEV1 /FVC% of all subjects were recorded by using a digital spirometer. For statistical analysis, unpairedt-test was performed. Results: The mean percentage of predicted value of FVC, FEV1 were significantly lower (p<0.001) in cotton dust exposed workers (CD-EW) than those of control. The mean percentage of predicted value of FEV1 / FVC% in CD-EW is slightly decreased compared to control but it was not statistically significant. Conclusions: From the result of this study it can be concluded that cotton dust (CD) may have harmful effects on some pulmonary function. Bangladesh Soc Physiol. 2016, June; 11(1): 35-38